Selection of the stability region of linear dynamic system with fractional order controllers - Lobok, Alexey; Goncharenko, Boris; Vikhrova, Larisa (My University, 2018)
The solution of the problem of the selection of the region of stable stabilization of linear dynamic systems with -regulator a factor of fractional order is presented. Using the D-partition method, we obtain the analytical formulas defining the boundaries of the stability domain of the system "object" + "fractional -regulator" in relation to the automatic control of the process of biological purification of contaminated water by active sludge. Some results of computational experiments are given, an estimation of efficiency of a fractional controller is given. Наводиться розв’язок задачі виділення області стійкої стабілізації лінійних динамічних систем з - регулятором дробового порядку. Використовуючи метод D-розбиття, отримані аналітичні формули, що визначають межі області стійкості системи "об'єкт" + "дробовий - регулятор" стосовно автоматичного керування процесом біологічного очищення забруднених вод активним мулом. Наведені деякі результати обчислювальних експериментів, дається оцінка ефективності дробового регулятора.
Keywords: stabilization domain; fractional derivatives; fractional integrals; PI-regulator; D-split method; область стабілізації; дробові похідні; дробові інтеграли; регулятор дробового порядку; PI- регулятор; метод D-розбиття; перетворення Лапласа для диферінтегратора; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка